Dynamics of the evolution of the strategic management concept: From the planning school to the neostrategic approach - Tomasz Kafel; Bernard Ziębicki (Journal of Entrepreneurship, Management and Innovation)
Purpose: Strategic management has been developing in business theory and practice for over 50 years. Presently, it constitutes the main area of research interest in management science. The contemporary conditions of business operations create new challenges for strategic management, such as the use of dynamic capabilities in strategy building, relational strategies, networking of organizations, technology development and automation of processes, and global strategies. These challenges are often referred to as neostrategic management. The purpose of this publication is to present the findings of research concerning new strategic management concepts and challenges. Methodology: The main research method of this article was a narrative literature review. On the basis of the research, the development of the concepts as well as contemporary trends and challenges of strategic management were characterized. There is also a synthesis of the problems and research results presented in the articles in this special issue of JEMI. Findings: Various schools and approaches to strategy formulation have been created. They indicate different factors that allow for success in strategic management such as: setting long-term goals, selection of programs and their execution plans (planning school); connection of the enterprise with the environment (evolutionary school); focusing attention on competitive advantage and achieved performance (position-based school); focus on one’s own resources and competences (resource school); use of opportunities and creating innovation (simple rules school); selection of the best option and orientation in business management (real options school); or eclectic perspectives, integrating the listed approaches. The strategic management concept has two dimensions. The first dimension is related to the emergence of subsequent, new strategic management concepts, which often hark back to the previous schools and approaches. The second dimension of development applies to operationalization and adjustment of the previous concepts to the changing conditions. Implications for theory and practice: The paper characterizes the research results presented in the articles included in this JEMI issue. They deal with various problems and challenges in the field of strategic management, such as the relationship between market dynamics, market orientation and performance of enterprises; the innovativeness of companies as a contemporary strategic orientation of companies; the strategy implementation and the management of the organization change; problems of strategic management of the development of the city. Originality and value: The problems presented in the study relate to challenges and new concepts in strategic management. They enrich the existing knowledge on the development of strategic management, and also create inspiration for further research in this area